The Influence of Product Quality and E-Money Payment Systems on Customer Satisfaction in Food & Beverage MSMEs at Blackballs Coffee Shop - Willy Ramdhani; Ahmad Rasyiddin; Dadah Muliansyah (Universitas Mohammad Husni Thamrin, 2025)
This study examines the influence of product quality and e-money payment systems on customer satisfaction at Coffee Shop Blackballs. The problem arose due to declining sales between July and December 2024, which encouraged an investigation into factors affecting customer satisfaction. The research applied an associative design using both primary and secondary data. Primary data were collected through questionnaires distributed to loyal customers, while secondary data were obtained from documentation. Analytical methods included validity and reliability tests, classical assumption tests, correlation analysis, coefficient of determination, multiple linear regression, and hypothesis testing using t-tests for partial effects and F-tests for simultaneous effects at a 5% significance level (α = 0.05). The regression equation obtained was: Y = 5.006 + 0.269X₁ + 0.646X₂, with X₁ = Product Quality, X₂ = E-money Payment System, and Y = Customer Satisfaction. The coefficient of determination indicated that product quality influenced satisfaction by 72.6%, while the e-money payment system contributed 79.8%. When tested simultaneously, both variables accounted for 81.1% of customer satisfaction. The t-test results confirmed that product quality (t = 14.903) and e-money payment systems (t = 18.218) significantly affect customer satisfaction. The F-test value of 177.918 > 3.96 also demonstrated a significant simultaneous effect. In conclusion, product quality and e-money payment systems positively and significantly affect customer satisfaction, both individually and jointly. These results suggest that improving product quality and optimizing digital payment systems are effective strategies to increase customer satisfaction and enhance sales performance at Coffee Shop Blackballs.